Pengaruh Pendidikan Kesehatan terhadap Pengetahuan Tentang Diet Diabetes Melitus Tipe 2 di Rsu Diponegoro 21 Klaten - Suryani, Indah; Yuliani, Feri Catur; Rusyani, Yeni; Akbar, Amin (TRIAGE Jurnal Ilmu Keperawatan, 2025)
Diabetes Mellitus is a degenerative disease that show a trend of increasing cases global, including in both developing and developed countries. It is a chronic, long-term disease characterized by metabolic system disorders and increased blood glucose levels. Health education is a process of conveying information aimed at changing habits, attitudes, and understanding of individual, community and national health. The aim of this study is to determine of the effect of health education of knowledge about type 2 diabetes mellitus at Diponegoro 21 hospital in Klaten. Methods research the method used in this Pre-experimental research. This research uses a pre-consult approach with a pretest-posttest design with Wilcoxon population consisting of type 2 diabetes mellitus patients at Diponegoro 21 Klaten Hospital in 2025, totaling 223 patients. Health education was delivered through leaflets. The result of the level of knowledge in type 2 diabetes mellitus patient showed that respondents were in the good category(77.4%). The results of the Wilcoxon P value test were (0.000) which means P<0.05, there is an effect of education on the level of knowledge about diet type 2 diabetes mellitus patient. Conclusion there is effect of health education on the level of knowledge about diet in patients with type 2 diabetes mellitus. The results of the study showed that there not found between theory and facts, respondents knowledge before being given health education is lacking and sufficient after being given health education.